MEMORY, ATTENTION, THINKING OF SCHIZOPHRENIA PATIENTS: CONNECTION WITH THE GENDER, ALCOHOL ABUSE AND POLYMORPHISM OF THE GENEM CATHEHOL-ORTHO-METHYLTRANSFERASE - A. A. Buleyko; V. A. Soldatkin; E. V. Mashkina; V. V. Kushchenko (Медицинский вестник Юга России, 2017)
Objective: analysis of the connection rs4860 Val158Met polymorphism of catechol-ortho-methyl transferase gene (COMT) with thinking, memory, attention of patients with schizophrenia taking into account comorbidity alcohol abuse and gender identity.Materials and methods: 200 patients with paranoid schizophrenia, 100 men and 100 women. Patients are distributed into subgroups by the factor of comorbidity alcohol abuse. Short-term memory, attention, thinking has been evaluated by psychometric scales. The variant of polymorphism rs4680 of gene COMT is determined by a genetic method. The subgroups were compared among themselves. The association of alcohol abuse, gender identity, genotype with features of these cognitive functions was investigated.Results: the study demonstrated a high prevalence of alcohol dependence in patients with schizophrenia. There is no clear direct effect of alcohol abuse on cognitive status. Gender peculiarities of the cognitive status of schizophrenic patients have been revealed. In men, the conjugation of the genotype Met158Met is noted with greater safety of short-term memory and attention against the background of more severe disorders of thinking in the schizophrenic type. Conclusions: the study did not confirm the significant effect of the comorbidity alcohol abuse on the cognitive processes of patients with schizophrenia. In men more severe short-term memory, attention disturbance predominate, unlike women who have a greater depth of schizophrenic thinking disturbances. The variant of Met158Met polymorphism is associated with relative safety of short-term memory and attention among men, without comorbidity alcohol abuse.